Species comparison: human and minipig PBMC reactivity under the influence of immunomodulating compounds in vitro - Pernold, Clara P. S.; Lagumdzic, Emil; Stadler, Maria; Dolezal, Marlies; Jäckel, Sven; Schmitt, Michael W.; Mair, Kerstin H.; Saalmüller, Armin (Frontiers in Immunology, 2024)
Considering the similarities between swine and humans, it is a logical consequence to use swine as a translational model in research and drug development, including non-clinical safety. Here, we compared the reactivity of peripheral blood mononuclear cells (PBMCs) from humans and minipigs under the influence of different compounds in vitro. We conducted a flow cytometry-based proliferation assay that focused on the T-cell response to three different stimuli: Concanavalin A (ConA), Phytohemagglutinin-L (PHA-L), and Staphylococcal Enterotoxin B (SEB). Furthermore, four approved immunosuppressive drugs -Abatacept, Belatacept, Rapamycin, and Tofacitinib -which are used for the treatment of rheumatoid arthritis or rejection in transplant recipients, were combined with the different stimuli. This allowed us to study the effect of suppressive drugs in comparison with the different stimuli in both species. We examined proliferating T cells (CD3 + ) and investigated the presence of TCR-αβ + and TCR-γδ + T cells. Differences in the response of T cells of the two species under these various conditions were evident. CD4 + T cells were more activated within humans, whereas CD8 + T cells were generally more abundant in swine. The effectiveness of the used humanized antibodies is most likely related to the conserved structure of CTLA-4 as Abatacept induced a much stronger reduction in swine compared to Belatacept. Rapamycin and Tofacitinib reduction of proliferation was highly dependent on the used stimuli. We further investigated the effect of the immunosuppressive compounds on antigen-specific restimulation of pigs immunized against Porcine Circovirus 2 (PCV2). Treatment with all four compounds resulted in a clear reduction of the proliferative response, with Rapamycin showing the strongest effect. In conclusion, our findings indicate that the effectiveness of suppressive compounds is highly dependent on the stimuli used and must be carefully selected to ensure accurate results. The results highlight the importance of considering the response of T cells in different species when evaluating the potential of an immunomodulatory drug.